2023
DOI: 10.3390/molecules28114439
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Variability and Chemotype Concept of Essential Oils from Algerian Wild Plants

Fatima Zahra Benomari,
Mathieu Sarazin,
Djamel Chaib
et al.

Abstract: The chemical compositions of eleven wild species of aromatic and medicinal plants indigenous to Algeria, including Thymus, Mentha, Rosmarinus, Lavandula, and Eucalyptus, were analyzed. The identification of the chemical composition of each oil was conducted using GC-FID and GC-MS capillary gas chromatography. The study investigated the chemical variability of the essential oils based on several parameters. These included the impact of the vegetative cycle on oil composition, variations among subspecies of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 44 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Moreover, many studies reported that the chemical composition and essential oils yield depend on age, circadian rhythm, soil, temperature conditions, plant organ, and extraction method, among others ( Benomari et al, 2023 ). Therefore, studies are necessary to analyze the influence of these factors on the chemical variability of essential oils, knowledge of which is essential for applying essential oils for phytotherapeutic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many studies reported that the chemical composition and essential oils yield depend on age, circadian rhythm, soil, temperature conditions, plant organ, and extraction method, among others ( Benomari et al, 2023 ). Therefore, studies are necessary to analyze the influence of these factors on the chemical variability of essential oils, knowledge of which is essential for applying essential oils for phytotherapeutic purposes.…”
Section: Introductionmentioning
confidence: 99%